1994
DOI: 10.4141/cjas94-042
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in intake and digestion of a high-roughage diet by muskoxen

Abstract: . 1994. Seasonal variation in intake and digestion of a high-roughage diet by muskoxen. Can. J. Anim. . We studied changes in body weight, intake, retention time and apparent digestibility of a supplemented brome-alfalfa hay by mature muskoxen held near Saskatoon, Saskatchewan during two seasonal cycles. Body weights and voluntary intake were monitored during 16 Le poids corporel moyen (+ ET) des femelles f6condes atteignait un maximum en f6vrier et en mars (248 ! 5 kg) et un creux imm6diatement aprds le vOl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 29 publications
4
30
1
Order By: Relevance
“…This confirms reports on penned animals by Christopherson et al (1978), which showed modest seasonality. Our data show peak voluntary intake and maintenance requirements in June and September (both years using both methods), a pattern more similar to muskoxen (Adamczewski et al 1994) than wapiti (spring, Jiang and Hudson 1994). Current data provide evidence that forage quality may override seasonal effects of photoperiod and ambient temperature.…”
Section: Energy Requirementssupporting
confidence: 57%
“…This confirms reports on penned animals by Christopherson et al (1978), which showed modest seasonality. Our data show peak voluntary intake and maintenance requirements in June and September (both years using both methods), a pattern more similar to muskoxen (Adamczewski et al 1994) than wapiti (spring, Jiang and Hudson 1994). Current data provide evidence that forage quality may override seasonal effects of photoperiod and ambient temperature.…”
Section: Energy Requirementssupporting
confidence: 57%
“…food intake and requirements in winter may therefore depend on the size of body stores and additional energy demands for locomotion and thermoregulation in nonreproductive animals Barboza and Hume 2006). Cycles of hyperphagia and hypophagia in muskoxen probably follow a common seasonal cue from photoperiod because the patterns for castrated males are similar to those of immature animals and adult females (Adamczewski et al 1994a;Rombach et al 2002b).…”
Section: Discussionmentioning
confidence: 95%
“…Low food intakes in winter should favor fiber digestion in northern ungulates such as muskoxen. Fiber digestibility of a common winter diet is greater in muskoxen than in cattle (Bos taurus) probably because food intakes and passage rates are lower in muskoxen than in cattle (Adamczewski et al 1994a(Adamczewski et al , 1994b. Degradation of fiber does not increase in muskoxen between autumn and winter; on the contrary, cellulose digestibilities decline from autumn (0.76 g g Ϫ1 ) to winter (0.65 g g Ϫ1 ; .…”
Section: Introductionmentioning
confidence: 93%
“…Although studies of muskox diet have shown muskoxen to be quite capable of utilizing willow during summer (Wilkinson et al, 1976;Thing et al, 1987;Larter and Nagy, 1997), a diet high in willow browse may not be advantageous. Muskoxen represent the classic grazer (Hofmann, 1989(Hofmann, , 2000: they have a large gut capable of processing large amounts of low-quality forage and a very slow rumen turnover rate (Adamczewski et al, 1994). Willow leaves and newly growing stems show a consistent increase in lignin content, which reaches 10 -25% by midAugust, whereas lignin content in sedge (Carex spp.)…”
Section: Discussionmentioning
confidence: 99%
“…Population estimates for muskoxen (Ovibos moschatus) (age > 1 year) on Banks Island increased from 29 168 (SE 2104) in 1985 to a peak of 64 608 (SE 2009) in 1994 and then declined to 45 833 (SE 1938) in 1998. From 1986to 1999, annual sex and age classification surveys of muskoxen were conducted during summer.…”
mentioning
confidence: 99%